2014
DOI: 10.12659/msm.889727
|View full text |Cite
|
Sign up to set email alerts
|

The presence of CD55- and/or CD59-deficient erythrocytic populations in patients with rheumatic diseases reflects an immune-mediated bone-marrow derived phenomenon

Abstract: BackgroundComplement has the potential to provoke severe impairment to host tissues, as shown in autoimmune diseases where complement activation has been associated with diminished CD55 and/or CD59 expression on peripheral blood cell membranes. The aim of this study was to evaluate the presence of CD55- and/or CD59-deficient erythrocytic populations in patients with different rheumatic diseases and to investigate possible correlations with clinical or laboratory parameters.Material/MethodsCD55 and CD59 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It is plausible that this could have aggravated the complement activation and related pathological manifestations in patients with CAD. A disease related decline in Cregs has earlier been reported in Rheumatoid arthritis (RA) (24, 25). Herein, we observed a significantly high surface expression of CD35 on granulocytes and of CD59 on lymphocytes and granulocytes of CAD patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is plausible that this could have aggravated the complement activation and related pathological manifestations in patients with CAD. A disease related decline in Cregs has earlier been reported in Rheumatoid arthritis (RA) (24, 25). Herein, we observed a significantly high surface expression of CD35 on granulocytes and of CD59 on lymphocytes and granulocytes of CAD patients.…”
Section: Discussionmentioning
confidence: 86%
“…Membrane complement regulatory proteins are expressed widely on different cell populations. Dysregulation of the Cregs, proteins responsible for maintaining homeostasis of the complement cascade, has been implicated in several autoimmune disorders, chronic inflammatory diseases, diabetes, cancers and malaria (11, 16, 18, 24, 25). Unabated activation of the complement cascade and increased expression of inflammatory cytokines contribute significantly to the immune inflammatory manifestations in CAD (4, 26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins propagate complement-mediated cell lysis and their deficiency or dysfunction has been associated with the pathophysiology of other diseases as well. [49][50][51][52][53] Most studies have focused on surface-bound complement regulators -CD55, CD59, CD46 and CR1 -. In the frame of SCD, some studies revealed decreased CD55 and CD59 on sickled erythrocytes, in comparison with control subjects.…”
Section: Underlying Mechanisms Of Complement Activation In Scd For Thmentioning
confidence: 99%